An annotated checklist of the Anthicidae and pediline Pyrochroidae (Insecta: Coleoptera) of Iran, with thirteen new country records - Telnov, Dmitry; Ghahari, Hassan (Zootaxa, 2018)
The fauna of Iranian Anthicidae and pediline Pyrochroidae (Coleoptera) is summarized in this paper. A total of 132 species from 19 genera and four subfamilies (Anthicinae, Notoxinae, Steropinae, and Tomoderinae) of Anthicidae and two species of Pedilinae are listed. Three new synonyms are proposed: Anthicus armatus Truqui, 1855 = A. pseudoarmatus Telnov, 2008 syn. nov., Notoxus hirtus LaFerté-Sénectère, 1849 = N. caucasicus Pic, 1900 syn. nov., Stricticomus rufithorax (LaFerté-Sénectère, 1849) = Anthicus transcaspicus var. subnotata Pic, 1910 syn. nov. One new combination is made: Nitorus unifasciatus (Desbrochers des Loges, 1875) comb. nov. (from Pseudoleptaleus Pic, 1900). Thirteen species are reported for the fauna of Iran for the first time: Anthicus armatus Truqui, 1855, A. episcopalis Pic, 1903, A. quadrispilus Marseul, 1879, Cyclodinus reitteri (Pic, 1892), Leptaleus klugii klugii LaFerté-Sénectère, 1849, Stricticomus araxicola (Reitter, 1889), S. arcuaticeps (Pic, 1900), S. herzi (Pic, 1905), Microhoria aphaenops (Pic, 1902), Tenuicomus finalis Telnov, 2003, Notoxus hirtus LaFerté-Sénectère, 1849, N. simulans simulans Heberdey, 1935, and Tomoderus scydmaenoides Reitter, 1878.